Orai–vascular endothelial-cadherin signaling complex regulates high-glucose exposure-induced increased permeability of mouse aortic endothelial cells. Issue 1 (22nd April 2021) - Wei, Yuan; Bai, Suwen; Yao, YanHeng; Hou, Wenxuan; Zhu, Junwei; Fang, Haoshu; Du, Yinan; He, Wei; Shen, Bing; Du, Juan
Abstract : Introduction: Diabetes-associated endothelial barrier function impairment might be linked to disturbances in Ca 2+ homeostasis. To study the role and molecular mechanism of Orais–vascular endothelial (VE)-cadherin signaling complex and its downstream signaling pathway in diabetic endothelial injury using mouse aortic endothelial cells (MAECs). Research design and methods: The activity of store-operated Ca 2+ entry (SOCE) was detected by calcium imaging after 7 days of high-glucose (HG) or normal-glucose (NG) exposure, the expression levels of Orais after HG treatment was detected by western blot analysis. The effect of HG exposure on the expression of phosphorylated (p)-VE-cadherin and VE-cadherin on cell membrane was observed by immunofluorescence assay. HG-induced transendothelial electrical resistance was examined in vitro after MAECs were cultured in HG medium. FD-20 permeability was tested in monolayer aortic endothelial cells through transwell permeability assay. The interactions between Orais and VE-cadherin were detected by co-immunoprecipitation and immunofluorescence technologies. Immunohistochemical experiment was used to detect the expression changes of Orais, VE-cadherin and p-VE-cadherin in aortic endothelium of mice with diabetes. Results: (1) The expression levels of Orais and activity of SOCE were significantly increased in MAECs cultured in HG for 7 days. (2) In MAECs cultured in HG for 7 days, the ratio of p-VE-cadherin to VE-cadherin expressed on the cell membrane and the FD-20 permeability in monolayer endothelial cells increased, indicating that intercellular permeability increased. (3) Orais and VE-cadherin can interact and enhance the interaction ratio through HG stimulation. (4) In MAECs cultured with HG, the SOCE activator ATP enhanced the expression level of p-VE-cadherin, and the SOCE inhibitor BTP2 decreased the expression level of p-VE-cadherin. (5) Significantly increased expression of p-VE-cadherin and Orais in the aortic endothelium of mice with diabetes. Conclusion: HG exposure stimulated increased expression of Orais in endothelial cells, and increased VE-cadherin phosphorylation through Orais–VE-cadherin complex and a series of downstream signaling pathways, resulting in disruption of endothelial cell junctions and initiation of atherosclerosis.